Penggunaan Metode Eksperimen Untuk Meningkatkan Literasi Sains Bagi Anak Usia 4-5 Tahun di TK Muslimat NU 57 Teja Timur Pamekasan - vina Rahmatika; Musayyadah, Musayyadah; Farida, Siti (E-JURNAL AKSIOMA AL-ASAS, 2025)
This study aims to examine the effectiveness of the "Rainbow Ice Cream" experimental method in improving scientific literacy among early childhood learners, specifically children aged 4–5 years at TK Muslimat NU 57 Teja Timur Pemakasan. Scientific literacy in early childhood is crucial for fostering curiosity, critical thinking, and a basic understanding of natural phenomena. This research adopts a descriptive qualitative approach, utilizing observation, interviews, and documentation as data collection techniques. The results show that the implementation of this experimental method successfully increased children's enthusiasm, exploratory skills, and comprehension of basic science concepts such as color mixing and changes in states of matter. Therefore, the Rainbow Ice Cream experiment method is proven to be effective for science learning activities in early childhood education settings. Keywords: experimental method, rainbow ice cream, scientific literacy, early childhood.